A new species in the grass feeding leafhopper genus Hecalus Stål from Pakistan (Cicadellidae: Deltocephalinae: Hecalini) - Naveed, Hassan; Islam, Waqar; Sohail, Kamran; Zhang, Yalin (Zootaxa, 2019)
A new leafhopper species Hecalus rawalakotensis sp. nov. is described and illustrated from Rawalakot, Azad Jammu and Kashmir, Pakistan. A key is provided to distinguish all species in this genus from Pakistan.